CONTEXT-SPECIFIC CLIMATE-SMART AGRICULTURE BUSINESS CASES IN ETHIOPIA: INSIGHTS FROM THE SCALA PROGRAM - Tesfaye, Lidya Ayalew; Jalango, Dorcas Anyango; Assefa, Berhanu; Mundia, Carolyne Wanjiru (2025)
Context-specific climate-smart agriculture business cases under the SCALA program translate Ethiopia’s CSA investment plan into actionable, gender- responsive investments in Adama (Oromia), Sofi (Harari), and Enebse Sar Midir (Amhara). Three interventions are prioritized: small-scale irrigation vegetables, climate-smart small ruminants (sheep and goats), and improved poultry, implemented through six common interest groups serving 180 households, most of them women. The package addresses rain-fed risk, land degradation, and rising climate extremes while aligning with NDC, NAP, the CSA roadmap, and LT- LEDS. Expected results include a 30 percent increase in vegetable yields, 25 percent gains in livestock and poultry productivity, a 40 percent rise in household income, and 4.5 hectares under efficient irrigation annually. An indicative economic appraisal shows strong viability with a benefit–cost ratio of about 2.8 and a three-year NPV near USD 340,000. Delivery is led by MoA, FAO, UNDP, and CIAT through input provision, capacity building, and M&E, with clear pathways for scaling via women-led groups and blended finance.